N,N′-Bis(3,5-dichlorobenzylidene)ethane-1,2-diamine - Hoong-Kun Fun; Reza Kia (Acta Crystallographica Section E, 2008)
The molecule of the title Schiff base compound, C16H12Cl4N2, lies across an inversion centre and adopts an E configuration with respect to the azomethine C=N bond. The imine groups are coplanar with the aromatic rings. Within the molecule, the planar units are parallel but extend in opposite directions from the dimethylene bridge. In the crystal structure, molecules are linked together by intermolecular C—H...Cl hydrogen bonds along the a axis.